Efeitos da atividade turística no Brasil : uma abordagem de shift-share econométrica (2006-2016) - Silveira, Emanuel Jhonata Gomes da (2019)
Given the macroeconomic effects created by tourism, especially in a beneficial way, the practice of tourism is increasingly present when the goal is to achieve economic development. Thus, having some microregions are more dynamic than others, regarding the degree of specialization and competitive advantages in the tourism services offered. The objective of this study is to verify the distribution of the formal employment of the tourism sector in the Brazilian microregions through the specialization and competition effects, and to identify, eventually, the space overflows to the neighboring microregions. For that, we used shift-share and a spatial econometric approach. Specifically, the components of specialization and competitiveness estimated by the shift-share will be used as dependent variables of the econometric model. The main results indicated positive effects in the structural component, in the period studied (2006-2016), so that 61.11% of the microregions obtained gains in the creation of formal employment related to tourist services. In the differential component tourism services constitute a sector with competitive advantages in 53.58% of the Brazilian microregions. Estimates of the spatial econometric models have shown that the locational quotient of tourism services, the average income and the diversity index are positively related to the degree of specialization of the micro-regions. The global spillovers resulting from these variables promote a spreading of the effects to neighboring regions contributing to a better economic performance of the adjacent microregions, which consequently significantly affects the tourist services sector, through specialization effect. Local overflows were captured by the SDEM model, demonstrating statistical significance for the percentage of workers with a higher level. The locational quotient was statistically significant, and inversely related to the competitive effect, in the SAR, SEM and SAC models. Negative overflows through the direct and total effect of the locational quotient were verified in the SDM model, and local spillovers in the SDEM model, justified by the fact of the positive externalities in the long term, stimulate greater competitiveness of the sector. From the results, it can be concluded that some microregions are more specialized and dynamic than others because of strategic factors, given the particularities that certain regions have and the qualification of labor.